Hubungan Asi Eksklusif, Imunisasi Dasar, Orang Tua Perokok Dengan Infeksi Saluran Pernapasan Akut (ISPA) Pada Bayi 0-24 Bulan di PUSKESMAS Bagu Tahun 2024 - Qarimah, Yendry Ahlatul; Priono, Risky Irawan Putra; Surasmaji, Lalu Irawan; Ariyanto, Suwondo (Bioscientist : Jurnal Ilmiah Biologi, 2025)
The aim of this study is to determine the relationship between exclusive breastfeeding, basic immunization, parental smoking, and the occurrence of Acute Respiratory Infections (ARI) in infants aged 0-24 months at the Bagu Health Center in 2024. This study is a quantitative research with an observational approach, using a cross-sectional design. The sample size for this study was 60 samples, selected using purposive sampling technique. The study was conducted at the Bagu Health Center, Central Lombok Regency, in September 2024. The data obtained were analyzed using the Chi-square test with a significance level of p<0.05. The results of this study showed that univariate analysis revealed that 33 (55.0%) children experienced ARI, 33 (50.8%) infants received exclusive breastfeeding, 47 (78.3%) respondents had complete basic immunization status, and 39 (65.0%) respondents had smoking parents. Bivariate analysis showed a significant relationship between exclusive breastfeeding and ARI with a p-value of 0.001 (PR: 0.307, 95% CI: 0.173-0.544). A significant relationship was also found between complete basic immunization and ARI with a p-value of 0.035 (PR: 0.553, 95% CI: 0.377-0.811). A significant relationship was also found between parental smoking and ARI with a p-value of 0.001 (PR: 3.904, 95% CI: 1.586-9.609).